2010
DOI: 10.1089/ten.tea.2009.0294
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure–Biomolecule Interactions: Implications for Tissue Regeneration and Nanomedicine

Abstract: Great strides are being made worldwide in our ability to synthesize and assemble nanoscale building blocks to create advanced materials with novel properties and functionalities. The novel properties of nanostructures are derived from their confined sizes and their very large surface-to-volume ratios. Nanostructured surfaces have also been shown to elicit more favorable and selective biomolecule and cellular responses than surfaces at coarser length scales. In the case of nanoscale ceramics and osteoblasts, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…">IntroductionNanostructured materials have exhibited significant potential for biomedical applications, rendering the investigation of nanostructure-biomolecule (nano-bio) interactions critical regarding both the efficacy and safety of nano-biomaterials [1][2][3][4]. In particular, nanoscale morphology has been shown to elicit significant biomolecular responses, as proteins appear to "sense" variations in the topography of their nanoscale environments, and alter their conformation and hence their function [5,6], accordingly. During the last decade, studies on these "morphology effects" have demonstrated the critical nature of surface curvature in affecting biomolecule adsorption, conformation, and activity [7][8][9][10][11].…”
mentioning
confidence: 99%
“…">IntroductionNanostructured materials have exhibited significant potential for biomedical applications, rendering the investigation of nanostructure-biomolecule (nano-bio) interactions critical regarding both the efficacy and safety of nano-biomaterials [1][2][3][4]. In particular, nanoscale morphology has been shown to elicit significant biomolecular responses, as proteins appear to "sense" variations in the topography of their nanoscale environments, and alter their conformation and hence their function [5,6], accordingly. During the last decade, studies on these "morphology effects" have demonstrated the critical nature of surface curvature in affecting biomolecule adsorption, conformation, and activity [7][8][9][10][11].…”
mentioning
confidence: 99%
“…Protein attachment on a biomaterial surface is largely dependent on factors like surface chemistry and topography [3,6,16]. Although other variables contribute to the adsorption of proteins, such as pH and protein concentration in the medium, proteins can be adsorbed due to electrostatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to a number of relevant factors such as surface chemical composition, surface morphology (topography) [3] and pH of the surrounding medium, surface charges appear to be the main physical factor influencing the binding of proteins to the scaffold. This electrostatic interaction (strength and type) between the proteins and the material surface can also be controlled by varying the concentrations of electrolyte solutions and the pH of the medium [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of the candidate next generation technologies would be nanotechnology. Nanotechnology-based modifications in surface morphology and structures of biomaterials have been demonstrated to induce distinctive behaviors and responses in biological cells (Debbage 2009;Nuffer & Siegel 2010). Nanoscale surface features may generate a biomimetic environment because they may mimic cell-to-cell, cell-to-protein, and cell-to-tissue interactions, including surface sensing and recognition as well as signal transfer occurring Date: Accepted 13 April 2012 To cite this article: Yamada M, Ueno T, Minamikawa H, Ikeda T, Nakagawa K, Ogawa T. Early-stage osseointegration capability of a submicrofeatured titanium surface created by microroughening and anodic oxidation.…”
mentioning
confidence: 99%
“…Res. 24, 2013, 991-1001 doi: 10.1111/j.1600-0501.2012.02507.x at a molecular level (Curtis & Wilkinson 2001;Stevens & George 2005;Vogel & Sheetz 2006;Dalby et al 2007;Nuffer & Siegel 2010). Nanofeatured surfaces are also expected to act as smart materials that selfregulate their affinity for different cell types, potentially allowing tissue-specific regeneration capability (Variola et al 2008;Kubo et al 2009;Biggs et al 2010;Hori et al 2010).…”
mentioning
confidence: 99%